The Effectiveness of Drill Method in Improving Language Students’ Listening Skills of News at the Islamic-Affiliated Middle Schools - Irma Heryani; Jimat, Jimat Susilo; Susi Darihastining (Journal of Language and Literature Studies, 2024)
This research aimed to investigate the effectiveness of the Drill method in improving junior high school students’ listening skills, particularly in the context of listening to the news. The focus was on eighth-grade students at MTsN 5 Kuningan. Observations indicated that these students generally exhibited low proficiency in news listening. To address this, the study employed an experimental approach, utilizing a quantitative research method. Data were collected through tests, employing specific research instruments such as test sheets, to evaluate the impact of the Drill method on student learning outcomes. The study involved 23 students, and the data processing techniques included statistical analysis, specifically using t-test tests. This was to determine the significant impact of the Drill method on enhancing students’ news listening skills. Results indicated a positive effect of the Drill method on students’ listening abilities. A comparative analysis was conducted between the traditional lecture method and the Drill method. It was found that the Drill method was more effective, as evidenced by a t-count of 366.82, which is significantly higher than the t-table value of 2.015. This suggests that the Drill method, through its practice-oriented approach using audio-visual media, facilitates better understanding and retention of theory and information from news sources, thereby improving news listening skills among junior high school students.